PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI DAMPAK PERNIKAHAN DINI TERHADAP KESEJAHTERAAN ANAK DI KABUPATEN KAMPAR: COMMUNITY EMPOWERMENT THROUGH EDUCATION ON THE IMPACT OF EARLY MARRIAGE ON CHILD DEVELOPMENT IN KAMPAR DISTRICT - Ahmad Zikri; Muslim Muslim; Afdhol Rinaldi; Dhiya Dwi Afifah; Risa Juita; Hafidza Sanshia Arum (LPPM Universitas Abdurrab, 2025)
This community service program aims to raise awareness about the impact of early marriage on child development in Kampar Regency, Riau Province. This program was implemented through socialization in three schools: SMA Negeri 1 Bangkinang Kota, SMA Negeri 3 Tapung, and MAN 3 Kampar. The methods used included counseling, group discussions, and provision of data-based educational materials and case studies. The results showed an increased understanding of the physical, psychological and social risks posed by early marriage. The dominant factors influencing early marriage include age at marriage (86%), education level (80%), family economic conditions (90%), access to sexual information (84%), and social norms and pressures (65%). The activity also succeeded in instilling in students an understanding of the importance of education and emotional readiness before marriage. The program recommends a sustainable approach through cross-sectoral cooperation to reduce the number of early marriages. Intensive education, policy support, and family economic empowerment are expected to improve the welfare of the younger generation.